Financial Conditions and Audit Report Lag: Evidence from Indonesia’s Non-Primary Consumer Sector - Nainggolan, Enos Parlindungan; Sinaga, Gilbert Johan Martin (Accounting Research Journal, 2026)
This study examines the effect of financial conditions, proxied by solvability, profitability, and liquidity, on audit report lag in non-primary consumer goods companies listed on the Indonesia Stock Exchange during the 2020–2022 period. The study employs a quantitative approach using secondary data obtained from audited financial statements, with a total of 321 firm-year observations selected through purposive sampling. Multiple linear regression analysis is applied to test the proposed hypotheses. The results show that solvability has a positive and significant effect on audit report lag, indicating that firms with higher leverage tend to experience longer audit delays due to increased audit complexity and risk. In contrast, profitability and liquidity have negative and significant effects on audit report lag, suggesting that firms with better financial performance and stronger liquidity positions tend to complete the audit process more efficiently and report in a more timely manner. These findings support agency theory and signaling theory, highlighting that financial risk and performance serve as important determinants of audit timeliness. Firms with higher financial risk are associated with longer audit delays, while firms with stronger financial conditions provide positive signals that encourage timely reporting. This study contributes to the literature by providing sector-specific evidence from the non-primary consumer goods industry in Indonesia during the post-pandemic period. The findings also offer practical implications for management, auditors, and regulators in improving the efficiency and timeliness of financial reporting in emerging markets.